2016
DOI: 10.1038/ncomms11906
|View full text |Cite
|
Sign up to set email alerts
|

Targeted proteomics identifies liquid-biopsy signatures for extracapsular prostate cancer

Abstract: Biomarkers are rapidly gaining importance in personalized medicine. Although numerous molecular signatures have been developed over the past decade, there is a lack of overlap and many biomarkers fail to validate in independent patient cohorts and hence are not useful for clinical application. For these reasons, identification of novel and robust biomarkers remains a formidable challenge. We combine targeted proteomics with computational biology to discover robust proteomic signatures for prostate cancer. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 47 publications
(56 reference statements)
3
95
0
1
Order By: Relevance
“…Of the proteins that had two peptides identified the majority had coefficients in agreement between the two peptides; for example, Apolipoprotein E had coefficients of À6.23E-05 and À9.73E-06 for significant disease VQAAVGT-SAAPVPSDNH and WVQTLSEQVQEELLSSQVT-QELR, respectively. However, complement factor H-related protein 2 had coefficients of 1.17E+00 and À3.71E-02 with opposing signs for ITCAEEGWSPTPK and TGDIVEFVCK, respectively; this could be due to the presence of multiple proteoforms, post-translational modifications, variations in proteolytic digestion efficiencies or inaccurate quantification as has previously been described by Kim et al (2016) and would require additional study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Of the proteins that had two peptides identified the majority had coefficients in agreement between the two peptides; for example, Apolipoprotein E had coefficients of À6.23E-05 and À9.73E-06 for significant disease VQAAVGT-SAAPVPSDNH and WVQTLSEQVQEELLSSQVT-QELR, respectively. However, complement factor H-related protein 2 had coefficients of 1.17E+00 and À3.71E-02 with opposing signs for ITCAEEGWSPTPK and TGDIVEFVCK, respectively; this could be due to the presence of multiple proteoforms, post-translational modifications, variations in proteolytic digestion efficiencies or inaccurate quantification as has previously been described by Kim et al (2016) and would require additional study.…”
Section: Discussionmentioning
confidence: 81%
“…(2011) have identified a five serum glycoprotein biomarkers signatures for predicting tissue PTEN status and diagnosis and grading that predicted patients with a Gleason score < 7 or > 7 with an AUC value of 0.78. A urine proteomic peptide panel assessed by targeted proteomics identified proteins to predict pT3 disease before radical prostatectomy with an AUC of 0.74 compared to PSA alone of 0.66 (Kim et al ., 2016). Additional studies by our group have identified a serum protein panel predictive of increased stage of PCa with AUC 0.74 (Fan et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGM4 was previously suggested as a prostate cancer biomarker, but results were inconsistent and revealed either significant over-expression 65 or under-expression [66][67][68][69] of TGM4 in PCa versus benign disease, or inconclusive results with the opposite directions based on different assays 70 . TGM4 was found down-regulated 1.7-fold in urinary extracellular vesicles of PCa and had AUC 0.58 to diagnose PCa on biopsy 66 .…”
Section: Cc-by-nc-mentioning
confidence: 99%
“…Nowadays, liquid biopsy is actively investigated for disease monitoring, and the analysis of key metabolites (molecules less than 1 kDa) in body fluids has become an important approach to improve the risk analysis and early diagnosis of disease [6,7]. For example, Sequeiros et al identified that ADSV-TGM4 combination in urinary extracellular vesicles could classify benign and prostate cancer patients with high sensitivity and specificity [8].…”
mentioning
confidence: 99%